Five Techniques of Osseodensification in One Case - Abdulkarim Sheikh Ibrahim; Mohamad Hassan Jaafo; Anas Abdo (University Library System, University of Pittsburgh, 2024)
Initial stability of implants is an important factor for the osseointegration of dental implants. Initial stability of implants can be lost when the bone is insufficient in cases of immediate implantation or when the bone density is insufficient, making it difficult to ensure good initial stability. Many techniques have been used to increase bone density. This study tested the use of five methods to increase bone density in one patient. This study concluded that the five methods used were effective in densifying the bone and achieving clinically acceptable primary stability in low-density bone.